Second-derivative laser-induced fluorescence spectroscopy combined with chemometrics for authentication of the adulteration of camellia oil. Issue 1 (1st January 2018) - Chen, Hui; Geng, Dechun; Chen, Tong; Lu, Daoli; Chen, Bin
ABSTRACT: In this study, second-derivative laser-induced fluorescence spectroscopy (SD-LIF) and its derivative intrinsic-ratiometric laser-induced fluorescence spectroscopy (IR-LIF) were developed for the qualitative and quantitative analysis of camellia oil adulterated with sunflower oil or rapeseed oil, respectively. In the qualitative analysis, three pure oils and two blended oils were successfully discriminated based on SD-LIF and linear discriminant analysis. The influence of fluorescence concentration quenching on the adulterant concentration analysis was discussed. IR-LIF was established by using 646 nm chlorophyll b fluorescence as the insensitive reference and proved to be an effective approach to reduce the possible quenching influence on the full spectrum. Then, the combination of IR-LIF and partial least squares regression was employed to determine the adulterant concentration, and the results were satisfactory. The plots of the observed versus predicted adulteration concentration values showed high linearity. Root-mean-square errors of prediction lower than 3% were achieved.